MENGKAJI TANTANGAN PROFESIONALISME GURU PADA PEMBELAJARAN ABAD 21: Studi Kasus - Elisabeth W. Lobo; Afryanti Karmoy; Roswita M. Bere Besin; Falentina Bone; Greyzella P. Humau; Filda E. Selan; Hiwa Wonda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Twenty-first century learning demanded a transformation in the role of teachers in line with technological advancements, the Industrial Revolution 4.0, and Society 5.0. Teachers were no longer positioned as the primary source of knowledge; instead, they functioned as facilitators who fostered critical thinking, creativity, communication, and collaboration skills (4C). However, in practice, teacher professionalism faced numerous challenges, including limited digital literacy, frequent curriculum changes, insufficient professional training, and disparities in educational facilities, particularly in remote, outermost, and underdeveloped regions (3T areas). This study aimed to examine the challenges of teacher professionalism in twenty-first century learning and to explore efforts undertaken to address them. The method employed was a literature review, conducted by analyzing various scientific sources such as peer-reviewed journals, books, and relevant research reports.